Sintesis Material Magnet Ba(Fe,Co,Zn)12O19 Sebagai Aplikasi Penyerap Gelombang Mikro - Serafim Christina (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Barium hexaferrite magnet is one of ferrite magnet which is mostly used as a magnetic storage. Barium hexaferrite is well-known as a permanent magnet material with good magnetic properties such as coercivity value and relatively large magnetization. In this research has been carried out the magnetic material of Barium M-Hexaferrite BaFe12-2xCoxZnxO19 has been done synthesis with mechanical milling method. Basic materials used in the synthesis of BaCO3, Fe2O3, Co3O4, ZnO doped with variation of mol fraction substitution Co and Zn in the amount of x = 0; 0.25; 0.5; 0.75; 1. Then mixing process was carried out for 1 hour in mixing media alcohol 70% and some of ball mill. Pressing process was carried out powder added some glue and given press force with weight 4.5 ton product a pellet with diameter 20 mm and thickness 2.5 mm. Next that mixture dried at temperature 120oC during 1 hour, calcination at temperature 750oC during 3 hours until got powder BaFe12-2xCoxZnxO19. Sintered process at temperature 1100oC and keep it as long as 5 hours in order happened reaction and then milling 0, 5, 10 and 30 hours. Results of XRD characterization identification that the peaks of barium ferrite crystal with a hexagonal crystal system and has single phase BaFe12O19 with doping concentration of x=0.25. The hysteresis curve from results of permagraph characterization shows that coercivity value decreased in the sample with doping concentration x=1. Analysis material absorber from VNA show the optimum value Reflection Loss for x=0 is -25.15 at 9.25 GHz.